Pengaruh pengalaman mengajar, penguasaan media pembelajaran dan produktivitas mengajar terhadap kinerja guru SD di Kecamatan Sewon Kabupaten Bantul - Sutarmi Sutarmi; Mundilarno Mundilarno (Universitas Sarjanawiyata Tamansiswa, 2016)
This research was aimed to determine: (1) the influence of teaching experience, mastery of learning media and productivity of teacher teaching on teachers terfomance of Elementary School, (2) the influence of teacher teaching experienceon perfomance of Elementary School, (3) the influence of teacher mastery of learning media perfomance of Elementary School, (4) the influence of productivity of teacher teaching perfomance of Elementary School. This research is a quantitative descriptive study. The variables in this research are teaching experience, mastery of learning media, productivity of teaching, and teachers perfomance.The population in this research is teachers of the State Elementary School in Kecamatan Sewon Kabupaten Bantul which amounts to 138 teachers. To make sample of this research is representative to the population’s member, sample was draw by using simple random sampling technique. Furthermore researcher choose 107 teachers of Elementary School in Kecamatan Sewon Kabupaten Bantul as sample of research. The dataacquisition were obtained via documentation and questionnaire. The data were analyzed by using the multiple linier regression formula involving three independent variabels and using the partial correlation formula, after testing the normality test, linearity test, and multycollinearity test. The result of data analysis shows that: (1) there is a positive and very significant influence of teaching experience, mastery of learning media and productivity of teacher teaching on teachers perfomance amounts 47,3%; (2) there is a positive and very signivicant teacher teaching experience to teacher performance amounts 23,2%; (3) there is a positive and very significant influence mastery of learning media of teacher teaching on teachers perfomance amounts 8,7%; (4) there is a positive and very significant productivity of teacher teaching on teachers perfomance amounts 15,4. The suggestion from researcher is the next researcher can reveal the unreveal relative contribution to get better result.